Kausalitas antara Live Streaming, Diskon, dan Gratis Ongkos Kirim terhadap Minat Beli Konsumen Shopee - Aliza R., Rahmina Puspa (Jurnal Ekonomi Dan Statistik Indonesia, 2024)
This study aims to examine the effect of live streaming variables, dis-counts, and free shipping on Shopee consumers' buying interest. The population in this study were people in Bandung who used the Shopee application. The sample type in this study used purposive sampling. De-termination of the number of samples using the Slovin formula resulted in 100 respondents being studied in this study. The research method used is descriptive analysis and multiple linear regression analysis which is processed using SPSS software version 26. The results of this study indicate that the live streaming and discount variables partially have no effect and yet significant on Shopee consumers' buying interest, while the free shipping variable has a positive and significant effect on buying in-terest. Simultaneously, the variables of live streaming, discounts and free shipping affect the buying interest of Shopee consumers. The Coefficient of Determination (R2) of 54.9% indicates that the live streaming, dis-count and free shipping variables provide almost all the information needed to predict the variance of the dependent variable (purchase in-tention).